Further delineation of HIDEA syndrome. Issue 12 (23rd September 2020) - Maddirevula, Sateesh; Ben‐Omran, Tawfeg; AlMureikhi, Mariam; Eyaid, Wafa; Arabi, Hisham; Alkuraya, Hisham; Alfaifi, Abdullah; Alfalah, Abdullah Hamed; Alsaif, Hessa S.; Abdulwahab, Firdous; Alfadhel, Majid; Alkuraya, Fowzan S.
Abstract: Recently, the genetic cause of HIDEA syndrome (hypotonia, hypoventilation, intellectual disability, dysautonomia, epilepsy, and eye abnormalities) was identified as biallelic pathogenic variants in P4HTM, which encodes an atypical member of the prolyl 4‐hydroxylases (P4Hs) family of enzymes. We report seven patients from four new families in whom HIDEA was only diagnosed after whole‐exome sequencing (WES) revealed novel disease‐causing variants in P4HTM . We note the variable phenotypic expressivity of the syndrome except for cognitive impairment/developmental delay, and hypotonia, which seem to be consistent findings. One patient only presented with hypotonia, developmental delay, and abnormal eye movements, which highlights the challenge in diagnosing milder cases with this new syndrome. Other notable features include mild facial dysmorphism, obesity, and brain dysmyelination and atrophy. We conclude that HIDEA is a highly variable syndrome and suspect that a large fraction of patients will be diagnosed via reverse phenotyping after recessive P4HTM variants are identified by agnostic genomic sequencing assays.